6 - Solidarity Messages - Journal system, (CODESRIA Bulletin, 2021)
Babatunde A. Ahonsi, Ph.D, Senior Program Officer The Ford Foundation Office for West Africa, Nigeria. Tove Strand, Director of NORAD, Norwegian Agency for Development Co-operation, Norway President, Sida Sweden Joseph R.A. Ayee, PhD, Professor / Dean Faculty of Social Studies, University of Ghana Helmi Sharawy, Arab Research Center Hage G. Geingob, Executive Secretary, Global Coalition for Africa Dr Lennart Wohlgemuth, Director & Dr Henning Melber, Research Director, The Nordic Africa Institute, Uppsala, Sweden For the Pan African Association of Anthropology, Dr. Socpa Antoine, Executive Secretary Alfred G. Nhema, Executive Secretary, OSSREA (Organization for Social Science Research in Eastern and Southern Africa) Nouria Remaoun, Centre Nationale de Recherche en Anthropologie Sociale et Culturelle, CRASC Oran, Algeria